2015
DOI: 10.3923/jps.2015.222.233
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tomato Plant Under Salt Stress: Role of Exogenous Calcium

Abstract: Salt stress is one of the most devastating abiotic stress which severely affects the agricultural productivity in various ways. A study was undertaken to investigate the tolerance and mitigation of salt stress in tomato by exogenous application of calcium (Ca 2+ ). The experimental results showed that salt stress significantly affects morphology, physiology and fruit weight of tomato. Plant height, leaf number and branch number/plant were decreased with increased levels of salinity mostly at 6 and 8 dS mG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 17 publications
6
23
0
Order By: Relevance
“…Results showed that, plant height was decreased under saline condition which was also found in tomato with increased levels of salinity mostly at 6 and 8 dS m -1 [17]. Similar results were also recorded in tomato [18], lettuce [19] and coriander [20].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Results showed that, plant height was decreased under saline condition which was also found in tomato with increased levels of salinity mostly at 6 and 8 dS m -1 [17]. Similar results were also recorded in tomato [18], lettuce [19] and coriander [20].…”
Section: Discussionsupporting
confidence: 72%
“…Saberi et al [26] also obtained reduced number of leaves plant -1 under salt stress. Leaf number was decreased under saline condition mostly at 6 and 8 dS m -1 in tomato [17]. So it is suggested that the SA application improved leaves production by reducing the effect of salt.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These opposite results can be explained by a genotype dependent response. In tomato, Parvin et al (2015) reported similar tendency indicating that the fruit weight is gradually decreased with the increased levels of salinity. In vegetable crops, it is well known that salt stress decreases marketable yield due to decreased productivity and an increased unmarketable yield of fruits, roots, tubers and leaves without commercial value (Machado and Serralheiro, 2017).…”
Section: Discussionmentioning
confidence: 73%
“…Number of leaves reduced is response to effect of salinity. Parvin et al, [29] and Jafari et al, [30] described similar outcomes. Glycine betaine help to reduce salinity and enhancing leaf numbers.…”
Section: Physiological Attributesmentioning
confidence: 67%